Civilized life in the universe : scientists on intelligent extraterrestrials - Basalla, George (Oxford University Press, 2006)
In this fascinating history of scientific speculation about intelligent extraterrestrial life from Plutarch to Hawking, Basalla traces the influence of one speculation on the next, showing an unbroken but twisting chain of ideas passed from one scientist to another, and from science to popular culture.